Oral Health-related Quality of Life in Relation to Oral Health Status among Residents in the Surrounding Areas of Rural Health Training Center Attached to a Medical College Hospital - Pathak, Anuja; Saxena, Vrinda; Jain, Manish; Tiwari, Vidhatri; Sharva, Vijayta; Upadhyaya, Shubhangi (Journal of Orofacial Research, 2015)
Background: The literature on oral health-related quality of life in relation to oral health status among rural population in India is scanty. Aims: To assess the oral health-related quality of life in relation to oral health status among residents in surrounding areas of a rural health training center attached to a medical collegehospital in Madhya Pradesh, India Materials and methods: This cross-sectional study was conducted over a period of 4 weeks among the residents in the surrounding areas of Rural Health Training Centre (RHTC), Ratua, attached to People’s College of Medical Science and People’s Dental Academy, Bhopal, Madhya Pradesh. A pilot study was conducted on a convenient sample of 20 participants at RHTC. The result of the pilot study enabled us to estimate the sample  size. The selection of participants was done using a stratified random sampling technique. The selected participants were interviewed by a calibrated investigator to collect the desired information on OHRQOL using the pretested OHIP-14 questionnaire. The oral health assessment was done using mouth mirrors, explores, and CPITN probe on a plastic chair under natural daylight by a calibrated investigator. The comparison of the mean values between different subgroups was done using independent sample t test and one-way analysis of variance (ANOVA). The comparison of the qualitative data between the different subgroups of the population was done using the chi-square test. The comparison of the mean values between different subgroups where the distribution was skewed wasdone using the Kruskal–Wallis test. Results: A total of 254 participants were examined in the present study. The mean OHIP-14 score was significantly higher (suggesting a higher oral health-related quality of life) among the participants without caries experience (p < 0.001). The mean OHIP-14 score significantly decreased (p < 0.001) as the periodontal status worsened. The mean OH1P-14 score was significantly lower (p = 0.017) among participants with oral mucosal lesions with no difference between participants with and without malocclusion. Conclusion: Oral health-related quality of life was poor among participants with oral diseases.